Evaluation of sweet potato (Ipomea batatas L. lam.) for potentials in flour, starch and cookie manufacture - Albor-Ma. Bautista, Maria Avelet B. (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2000)
Fresh sweetpotatoes (Ipomoea batatas (L.) Lam.), particularly Super Bureau variety, were processed into sweetpotato starch (SPS) and sweetpotato flour (SPF) utilizing mechanical drying and wet extraction method, respectively. The moisture content, physico-chemical parameters (namely the pH, pasting characteristics, and the gelatinization point) and color were determined. The resulting starch and flour were further tested for their feasibility in the manufacture of drop cookies. Different combinations of composite flour were were used to evaluate which level of substitution of all-purpose flour (APF) with sweetpotato flour (SPF) or sweetpotato starch (SPS) could be most desirable to the consumers. Treatments containing 100% (APF) (T1); 75% APF and 25% SPF (T2); 75% APF and 25% SPS (T3); 50% APF and 50%SPF (T4); 50% APF and 50% SPS (T5); 25% APF and 75% SPF (T6); 25% APF and 75% SPS (T7); 100% SPF (T8); and 100% SPS (T9) were evaluated for spread ratio, cookie height, color evaluation, and sensory characteristics. Final moisture content of 7.0% was obtained from both SPF and SPS with the pH of SPF being lower (5.8) than that of SPS (6.4). In terms of the gelatinization temperature, SPF established a much higher value as compared to SPS. Rapid visco analyzer disclosed SPS as having lower pasting attributes correlating it to poor eating quality. Furthermore, SPF exhibited higher resistance to breakdown and higher tendency towards retrogradation as compared to SPS. Color evaluation via Munsell Color File revealed SPF as having more distinctive darker color than SPS. Drop sweetpotato cookies evaluation indicated significant differences in spread ratio and the cookies height among nine treatments. The trend indicated bigger spread in treatments utilizing sweetpotato starch as compared to sweet potato flour. The general trend in terms of color showed that SPF-substituted cookies were darker in color than SPS-substituted ones. Descriptive polygons (spider graph) of the nine (9) treatments showed that 25% level of wheat flour substitution by SPF (T2) had a very similar profile with the control (T1, 100% All-purpose flour).